Excessive Inorganic Phosphate Burden Perturbed Intracellular Signaling: Quantitative Proteomics and Phosphoproteomics Analyses - Hetz, Rebecca; Beeler, Erik; Janoczkin, Alexis; Kiers, Spencer; Li, Ling; Willard, Belinda B.; Razzaque, Mohammed S.; He, Ping (Frontiers in Nutrition, 2022)
Inorganic phosphate (Pi), an essential nutrient for the human body, exerts adverse health effects in excess and deficit. High Pi-mediated cytotoxicity has been shown to induce systemic organ damage, though the underlying molecular mechanisms are poorly understood. Here we employed proteomics and phosphoproteomics to analyze Pi-mediated changes in protein abundance and phosphorylation. Bioinformatic analyses and literature review revealed that the altered proteins and phosphorylation were enriched in signaling pathways and diverse biological processes. Western blot analysis confirms the extensive change in protein level and phosphorylation in key effectors that modulate pre-mRNA alternative splicing. Global proteome and phospho-profiling provide a bird-eye view of excessive Pi-rewired cell signaling networks, which deepens our understanding of the molecular mechanisms of phosphate toxicity.